173k views
2 votes
Which of the following systems of equations has the solution (1, 4)?

y = –3x – 1
y = –x + 5
y = 3x + 1
y = –x + 5
y = 3x + 1
y = x – 5
y = 3x + 1
y = –x – 5

1 Answer

6 votes

Answer:

y = 3x + 1

y = -x + 5

Explanation:

Take the system of equations and substitute (1 ,4) in any one of the equations. If both the sides are justified, then (4,1) is the solution to that pair of equations.

1) y = -3x - 1 ---------(I)

y = -x + 5

Substitute (1,4) in equation (I)

4 = -3*1 - 1

4 = -3-1

4 ≠ -4

So, (1, 4) is not a solution.

2) y = 3x + 1 ---------------(II)

y = - x + 5

Substitute (1 ,4) in equation (II)

4 = 3*1 + 1

4 = 3 + 1

4 = 4

(1 ,4) is the solution for this system of equation.

User Saifullah Khan
by
4.7k points